(untitled) - Lasher, William R. (United States, 2008)
This book introduction to financial management, discounted cash flow and the value of securities, business investment decisions - capital budgeting, long-term financing issues...
Keywords: Business enterprises,Finance,Corporations,Doanh nghiệp kinh doanh,Tài chính,Doanh nghiệp; Finance,Finance,Tài chính,Tài chính